Leptin:Adiponectin Ratio and Metabolic Syndrome in the General Japanese Population - Kotani, Kazuhiko (The Korean Society for Laboratory Medicine, 2011)
BACKGROUND: Circulating leptin:adiponectin ratio (L:A) is a potential surrogate marker for cardiometabolic diseases; however, the relationship of the L:A with the occurrence of metabolic syndrome (MetS) has not yet been fully explored in the general Japanese population. METHODS: We enrolled 678 Japanese subjects (208 men and 470 women, mean age: 58.8±14.4 [SD] yr; mean body mass index: 23.6±3.3 kg/m(2)) in this study, and determined their MetS status by using the National Cholesterol Education Program-Adult Treatment Panel (NCEP-ATP) recommendations with minor modifications for the Japanese population. Biochemical markers such as leptin and adiponectin present in blood were measured. The statistical analyses performed were gender-based. RESULTS: A in subjects with MetS was significantly higher than that in subjects without MetS, regardless of gender. The L:A also showed a significant and gradual increase corresponding to the increase in the number of components of MetS present in both the genders (trend P<0.01). The cut-off level of the L:A to detect MetS was 0.59 (sensitivity: 0.72, specificity: 0.70) in men and 1.04 (sensitivity: 0.72, specificity: 0.69) in women. CONCLUSIONS: These results suggest that the L:A can serve as a clinically useful marker for detecting MetS characteristics in the general Japanese population. The clinical application of this laboratory index for detecting MetS should be assessed in future studies.